Enhanced thermal storage for residential heating: sand and iron waste to manage PV surpluses - Bruno, Roberto; Jaskhec, Gerald (Frontiers in Energy Research, 2025)
This research investigates the application of solid thermal storage, charged with a surplus of photovoltaic electricity, for residential building heating. The performance of the storage system was evaluated using TRNSYS modelling and simulation across various operating conditions, examining the impact of the installed photovoltaic peak power, storage volume and operating temperature. The solid storage medium was either pure sand or a sand-iron waste mixture. Results indicate the technology’s potential to improve renewable energy self-consumption and reduce dependence on fossil fuels, achieving a solar fraction for heating reaching 65% for a 49.5 kWp photovoltaic field and a 2 m3 storage unit at 600 °C. Economic analysis confirms the system’s viability in certain applications, in light of a discounted payback of 12 years, determined considering a lifespan of 25 years.